Polymer handbook - Brandrup, J.; Immergut, E. H.; Grulke, Eric A. (Wiley, 1999)
The Polymer Handbook is the single most comprehensive source of physical property data for polymers commercially available, with experimentally determined and selected data of about 350 properties for over 2,500 polymers. It contains a vast array of data for polymers, monomers and other ancillary topics that are required for experimental and theoretical research and applications of polymers. This is a must have database for all technologists, scientists, researchers, and students concerned with theoretical or applied polymer science. Knovel has made the entire book available online as a PDF and have used the Wiley Database of Polymer Properties as a source of its Interactive Tables. -- Provided by publisher.
Keywords: Polymers -- Tables.; Polymerization -- Tables.; elektronické knihy; electronic books